On the Efficiency of the Advanced TWA Approach to the 60-GHz Microstrip Antenna Analysis for 5G Wireless Communication Systems - Ayari, Mohamed (Engineering, Technology & Applied Science Research, 2023)
The bandwidth demand in mobile wireless applications has grown at an astounding rate due to the fast evolution of technology, spurring the antenna design fields. The approaches associated with realizing antenna structure at mm-Wave frequency bands for future 5G cellular devices present advantages and disadvantages. This paper exhibits a fast and original approach based on the transverse wave formulation called-up Advanced Transverse Wave Approach (ATWA). A compact 5G patch antenna is designed, measured, simulated, and analyzed in the context of unlicensed mm-wave ISM-band applications. Compared to recently published works, the obtained result analysis proves the efficiency of the proposed method in terms of calculation accuracy, computational efficiency, and peak memory usage and the overall good performance of the proposed antenna.